Systematic review and meta-analysis of pre-clinical research: the need for reporting guidelines - Percie du Sert, Nathalie (Eur Heart J, 2011)
Animal studies should be reviewed more objectively before embarking on human clinical trials, hence the need for guidelines argues the NC3Rs